IMPLEMENTASI PEMANFAATAN MEDIA TEKA TEKI SILANG (TTS) ONLINE DALAM MATAKULIAH NEUROSAINS UNTUK MAHASISWA CALON GURU RAUDHATUL ATHFAL (RA) - Sri Maryanti; Dede Trie Kurniawan (AWLADY : Jurnal Pendidikan Anak, 2017)
This study aimed to describe the use of crossword puzzle application (TTS) Online for prospective teachers Raudhatul RA (RA) State Islamic University Sunan Gunung Jati Bandung. The focus of this study is to describe the response of RA student teachers to use TTS Online. TTS application is made through Crossword Eplicse software and integrated online through http://bumibiologi.weebly.com/neurosains.html. (RA) Raudhatul student teachers in question is the fourth semester students contracting courses neuroscience  2016-2017. Neuroscience courses a neural science that studies the nervous system, especially the study of neurons or nerve cells with a multidisciplinary approach. Data collection techniques are: 1. Direct observation, 2. Questionnaire, 3. Analysis of documents 4. Test Shaped TTS. Based on data and analysis of the results conducted in two classes, namely class A and class B of the obtained findings that TTS Online research can increase the interest of the student teachers RA subjects neuroscience. Providing student responses that use TTS Online is very useful for their lectures. Use of this Online TTS in feel easy and precise in neuroscience lecture. Students assess one technique using perkulihan with Online TTS is already well in its application